Kinetics of the Reduction of die Zinc Oxide in Zinc Ferrite with Iron - J. R. Donald (The Minerals, Metals and Materials Society, 1995)
Electric arc furnace (EAF) dust, which can be considered as a by-product of the steel recycling process, contains significant quantities of recoverable zinc and iron, as well as hazardous elements such as cadmium, lead and chromium, which can be leached by ground water. The zinc in the EAF dust is found almost entirely in the form of either zinc oxide or zinc ferrite, the latter accounting for 20 to 50 percent of the total zinc. It is important that an efficient process be developed which renders the dust inert, while reclaiming the valuable metals to off-set processing costs. During the conventional carbothermic reduction processes, iron is formed, and this iron can participate in the reduction of the zinc oxide in zinc ferrite. In the present work, the reduction of the zinc oxide in zinc ferrite by iron according to the following reaction: ZnO-Fe2O3(s,s) + 2 Fe(s) = Zn(g) + 4 FeO(s) was studied in an argon atmosphere using a thennogravimetric technique. First, a thermodynamic analysis was performed using the F*A*C*T computational system. Then, the effects of briquette aspect ratio (lid), temperature, zinc ferrite particle size, amount of iron added, as well as additions such as lime, sodium chloride, and calcium fluoride were investigated. It was found that, initially, the reaction was chemically controlled with an activation energy of 178.1 kJ/mol. Then, after a product layer had formed on the outer surface of the briquette, the reaction was restricted by the diffusion of zinc gas away from the reaction interface. The parabolic rate law was fitted to the experimental data, and the parabolic rate constant was found to be: = -6.2275 + 0.0054 T (K)